Developing and validating an abbreviated version of the Microscale Audit for Pedestrian Streetscapes (MAPS-Abbreviated). (June 2017) - Cain, Kelli L.; Gavand, Kavita A.; Conway, Terry L.; Geremia, Carrie M.; Millstein, Rachel A.; Frank, Lawrence D.; Saelens, Brian E.; Adams, Marc A.; Glanz, Karen; King, Abby C.; Sallis, James F.
Abstract: Purpose: Macroscale built environment factors (e.g., street connectivity) are correlated with physical activity. Less-studied but more modifiable microscale elements (e.g., sidewalks) may also influence physical activity, but shorter audit measures of microscale elements are needed to promote wider use. This study evaluated the relation of an abbreviated 54-item streetscape audit tool with multiple measures of physical activity in four age groups. Methods: We developed a 54-item version from the original 120-item Microscale Audit of Pedestrian Streetscapes (MAPS). Audits were conducted on 0.25–0.45 mile routes from participant residences toward the nearest nonresidential destination for children (N=758), adolescents (N=897), younger adults (N=1655), and older adults (N=367). Active transport and leisure physical activity were measured with surveys, and objective physical activity was measured with accelerometers. Items to retain from original MAPS were selected primarily by correlations with physical activity. Mixed linear regression analyses were conducted for MAPS-Abbreviated summary scores, adjusting for demographics, participant clustering, and macroscale walkability. Results: MAPS-Abbreviated and original MAPS total scores correlated r=.94 The MAPS-Abbreviated tool was related similarly to physical activity outcomes as the original MAPS. Destinations and land use, streetscape and walking path characteristics, and overall total scores were significantly related to active transport in all age groups. Street crossing characteristics were related to active transport in children and older adults. Aesthetics and social characteristics were related to leisure physical activity in children and younger adults, and cul-de-sacs were related with physical activity in youth. Total scores were related to accelerometer-measured physical activity in children and older adults. Conclusion: MAPS-Abbreviated is a validated observational measure for use in research. The length and related cost of implementation has been cited as a barrier to use of microscale instruments, so availability of this shorter validated measure could lead to more widespread use of streetscape audits in health research. Highlights: MAPS-Abbreviated is a validated observational measure for use in research. This shorter measure could lead to more widespread use of streetscape audits. Microscale attributes were consistently associated with active transportation.